2000
DOI: 10.1046/j.1526-0984.2000.72001.x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Soil Geochemical Anomalies in the Mesa Quadrangle, Arizona, Using NURE Data

Abstract: Maps showing anomalously high concentrations of 13 different elements in soils within the Mesa Quadrangle of southern Arizona were constructed using information contained in the National Uranium Resource Evaluation (NURE) database. Existing geochemical databases such as NURE provide an inexpensive and accessible resource that can be used to characterize an area geochemically. Anomalies in soils were determined after applying descriptive statistics, logarithmic transformations, elimination of outliers, and mani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…National geochemical databases consisting of chemical composition of a grid of samples became available to the U.S. in 1994 (Hoffman et al, 1994) and in Chihuahua, Mexico, in 2001(SGM, 2001. Although these databases were originally intended for geochemical exploration purposes, they were later found to provide an inexpensive and accessible information source for conducting geochemical characterization (Borrego and Gutiérrez, 2000;Xuejing and Hangxin, 2001). Within the Rio Conchos basin, sediment geochemistry and geospatial (GIS, remote sensing) studies are just as scarce as those of water quality.…”
Section: Remote Sensing Gis and Sediment Geochemistrymentioning
confidence: 99%
“…National geochemical databases consisting of chemical composition of a grid of samples became available to the U.S. in 1994 (Hoffman et al, 1994) and in Chihuahua, Mexico, in 2001(SGM, 2001. Although these databases were originally intended for geochemical exploration purposes, they were later found to provide an inexpensive and accessible information source for conducting geochemical characterization (Borrego and Gutiérrez, 2000;Xuejing and Hangxin, 2001). Within the Rio Conchos basin, sediment geochemistry and geospatial (GIS, remote sensing) studies are just as scarce as those of water quality.…”
Section: Remote Sensing Gis and Sediment Geochemistrymentioning
confidence: 99%
“…This is because industrial operations involving the separation of metals from gangues such as iron from iron ore, through heating and smelting produces very large amount of particulate metals and other air pollutants (OECD, 1990). Ferrous and nonferrous smelters for instance, emit large quantity of arsenic, lead, cadmium and other heavy metals into the environment, except where highly efficient pollution control equipment are used (Borrego, 1998;Pacyna and Pacyna, 2001;Vaisman and Lacerda, 2003). Nriagu (1989) reported that, the smelting of copper and other nonferrous metals, release an estimated six million tons of sulphur dioxide (SO 2 ) into the atmosphere each year, which sums up to about 8% of total worldwide emissions.…”
Section: Introductionmentioning
confidence: 99%